PEMAKAMAN VERTIKAL SEBAGAI TIPOLOGI BARU - Sri Arta Utami Nofitasari; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2022)
A cemetery is the final resting place of the deceased. Death is part of the land of the dead. Death is one of the phases in the cycle of human life that all humans will face and experience. Death is one part of the process of human life. Death is a process that cannot be avoided by humans, humans who are born in the world will eventually leave the world. All living things believe that one day they will die. Humans cannot determine when they are born and when they will die. There are several ways of burial such as cremation, recommission, the burial of the grave, and others. But over time the land for burial has run out. Therefore, vertical burial facilities are Designed as a new typology and are expected to answer the problem of lack of burial land. The city of Jakarta is one of the cities that have limited land in Indonesia. A limited land is a form of increasing population in the city of Jakarta. The population continues to increase in proportion to the need for land for burials. Indonesia officially recognizes the existence of 6 Indonesian religions, this affects the way people have funerals with religious funerals. The funeral that is usually carried out is a funeral based on religion. The Design method used is by conducting a literature study; Literature Review; Area Analysis; Site Investigation; data collection and study of precedents. The results of the writing can be concluded that vertical burial is effective in overcoming the problem of shortage of burial land. Keywords: Burial; Death; Religious Architecture; Typology; Vertical AbstrakPemakaman adalah tempat peristirahatan terakhir orang yang sudah meninggal. Meninggal yaitu bagian dari kematian, Kematian merupakan fase dalam siklus kehidupan manusia yang pasti akan dihadapi dan dialami oleh seluruh manusia. Kematian merupakan salah satu bagian dari proses kehidupan manusia. Kematian adalah proses yang tidak bisa dihindari oleh manusia, manusia dilahirkan di dunia pada akhirnya akan meninggalkan dunia. Semua makhluk hidup percaya bahwa suatu hari mereka akan mati. Manusia tidak memiliki kemampuan untuk menentukan kapan dia lahir dan kapan mereka akan mati. Ada beberapa cara pemakaman seperti kremasi, resomasi, pemakaman kubur dan lainnya. Namun seiring waktu lahan untuk pemakaman telah habis. Maka, dirancang fasilitas pemakaman vertikal sebagai tipologi baru dan diharapkan menjawab permasalahan kurangnya lahan pemakaman. Kota Jakarta merupakan salah satu kota yang mengalami keterbatasan lahan di Indonesia. Keterbatasan lahan adalah bentuk dari peningkatan jumlah penduduk di Kota Jakarta. Jumlah penduduk terus meningkat sebanding dengan kebutuhan lahan untuk pemakaman. Indonesia secara resmi mengakui adanya 6 agama Indonesia, ini mempengaruhi cara pemakaman masyarakat dengan pemakaman agama. Pemakaman yang biasa dilakukan adalah pemakaman berdasarkan agama. Metode perancangan yang digunakan adalah dengan melakukan studi Literatur; Kajian Literatur; Analisa Kawasan; Investigasi Tapak; pengumpulan data dan studi preseden. Hasil dari penulisan dapat disimpulkan bahwa pemakaman vertikal efektif dalam mengatasi masalah kekurangan lahan pemakaman.